Unraveling Organizational Behavior Problems in Startup Agencies Through Analysis Methods and Literature Studies - Zahra Nabilla; Achmad Husen; Dian Alfia Purwandari; Bheni David Dwiana; Luthfi Jusniar Dwiputri (Jurnal Syntax Admiration, 2025)
This study examines organizational behavior problems in startup agencies through a descriptive-analytical approach that combines field observation and literature study. The focus of the research is to identify the key challenges in managing human resources in startups, including unfair employment policies, unclear employee status, weak supervision, ineffective communication, and inadequate work facilities. The research method involves informal discussions with employees and an in-depth analysis of various theories of organizational behavior. The results of the study show that organizational behavior problems in startup agencies are systemic and interrelated. The analysis revealed eight critical factors that cause problems: unstable leadership, ineffective internal communication, immature organizational culture, role ambiguity, high turnover, weak conflict management, limited human resource development, and excessive work culture that leads to burnout. Based on these findings, the research offers a comprehensive solution that includes job description redesign, two-way communication systems, compensation adjustments, work-life balance programs, human resource development, participatory supervision, and HR technology implementation. The contribution of this research lies in the provision of an integrated solution framework based on systemic and positive approaches in organizational behavior. The proposed solution is specifically designed for the dynamic startup agency context, with an emphasis on sustainability and employee well-being. This research is expected to be a reference for practitioners in creating a healthy, productive, and adaptive work environment in startups.